Respuesta :

i hope this is correct



Simplifying (2x + -1)(x + -3) = 18 Reorder the terms: (-1 + 2x)(x + -3) = 18 Reorder the terms: (-1 + 2x)(-3 + x) = 18 Multiply (-1 + 2x) * (-3 + x) (-1(-3 + x) + 2x * (-3 + x)) = 18 ((-3 * -1 + x * -1) + 2x * (-3 + x)) = 18 ((3 + -1x) + 2x * (-3 + x)) = 18 (3 + -1x + (-3 * 2x + x * 2x)) = 18 (3 + -1x + (-6x + 2x2)) = 18 Combine like terms: -1x + -6x = -7x (3 + -7x + 2x2) = 18 Solving 3 + -7x + 2x2 = 18 Solving for variable 'x'. Reorder the terms: 3 + -18 + -7x + 2x2 = 18 + -18 Combine like terms: 3 + -18 = -15 -15 + -7x + 2x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -15 + -7x + 2x2 = 0 Factor a trinomial. (-3 + -2x)(5 + -1x) = 0

Answer:

x<=-7

Step-by-step explanation:

2(x- 1) – (–x- 5) ≤ –18

Open the bracket

2x -2+x+5<= -18

3x +3<= -18

Then we will collect the like term

All the x variable should be on the left hand side and all the constant should be on the right hand side

Thus;

3x<=-18-3

3x<= -21

Divide both side of the equation by the coefficient of x

3x/3 <= -21/3

X <= -7